IDENTIFIKASI PENGARUH PENAMBAHAN SUSU SKIM PADA SIFAT FISIK, KIMIA, DAN ORGANOLEPTIK YOGHURT - Sari, Yuli Perwita; Candraruna, Dipta Bthari; Imani, Meida Indika; Maharani, Renata; Afifah, Zahrotul Umah Fifin; Rahman, Arif (Pro Food, 2024)
Yoghurt is a popular fermented milk product highly valued for its nutritional content and practical advantages. There is a demand for yoghurt products that suit the needs of a high-protein and low-fat diet. It also has a preferred texture, which is increasing along with consumer awareness about the importance of maintaining health. The addition of skim powder, apart from being a source of lactose, can incline the rheological properties of yoghurt, minimize the occurrence of syneresis, and increase aroma, acidity, protein, and optimize the work of lactic acid bacteria. This study aimed to identify the effect of adding 2% (w/w) or 6 gr and 4% (w/w) or 12 gr skim milk on the yoghurt's characteristics. Yoghurt was made by adding 10 g of sugar and 13 mL of 1:1 culture of Streptococcus thermophilus and Lactobacillus bulgaricus, then incubating at 37 ºC for 17 hours. Variations in the addition of 6 and 12 g of skim milk powder can affect the total solids and pH of the yoghurt, while the water and protein content were relatively the same. Adding skim milk in different amounts did not make any difference in all organoleptic properties. Yoghurt with 6 gr or 2% skim milk is preferred because of its taste, viscosity, and overall characteristics.